(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
Communication is natural to the species of human beings. Language is used for expressing and sharing ideas, beliefs and thoughts. A lot of interaction goes on in natural conversational situations. Hence, language has to be used very carefully. In order to maintain smooth communication flow and good relationships, it is necessary to be polite while conversing. However, the concept and strategies of politeness are different in different cultures and also vary from individual to another. Learners from one language community fail to understand the idea of politeness while learning a second or foreign language. In this study, the researchers have analysed natural conversational extracts of fourteen Iraqi college students majoring in English, which they study as a foreign language and tried to conclude the reasons why they are confused while using the politeness principle in English. The study concluded with some suggestions to teachers of English at Iraqi colleges departments majoring in English and syllabus designers at the Iraqi ministry of higher education.